PERANCANGAN PROTOTIPE KENDARAAN LISTRIK BERODA TIGA - Didi Widya Utama; Jan Antonius; Danardono Agus Sumarsono (Jurnal Ilmiah Teknik Mesin POROS, 2014)
Abstract: Pollution levels over time has been increased. One of the causes of the pollution are Internal combustion engine vehicle. In Indonesia, the air pollution produced by motor vehicles approximately 55 micrograms per cubic meter CO2. One of the solution to overcome the pollution problem is to create environmentally friendly vehicles using electric motor. In this paper will discuss about the design of a concept of environmentally friendly personal vehicle, which is used 3 wheel and can carry a single passenger. The process is design using the CAD software in three dimensional design, then static analysis was conducted using FEA to produce the maximum stress and the critical location due to the load from the design of the vehicle.